COMPOSIÇÃO DO LEITE DE VACAS DA RAÇA JERSEY MANEJADAS EM DISTINTAS INTENSIDADES DE PASTEJO - Zenzen, Angelo M.; Bortolin, Felipe; Juswiak, Patrícia; Bergoli, Luís M. G.; Kuinchtner, Bruno C.; Diefenbach, Jairo; Richards, Neila S. P. d. S.; Sartori, Cesar O.; Maixner, Adriano R.; Berto, Jorge L. (Salão do Conhecimento, 2013)
Resumo